ENTREPRENEURSHIP EDUCATION IN UKRAINE IN TERMS OF GLOBALIZATION - Riabova, Yulia (Педагогічна освіта: теорія і практика, 2020)
In the article entrepreneurship education in Ukraine in terms of globalization is considered. New challenges in the system of training of future specialists are driven by socio-cultural dynamics, which are constantly accelerating under the pressure of globalization and the information revolution. In the context of globalization, competition in the field of educational services is increasing. In the context of society’s search for an effective educational policy and the need for a transition to flexible high-tech education the latest information and communication technologies should be used. Political scientists define globalization as an objective process of restructuring and qualitative development of the international environment and socio-economic system. New approaches need to solve the existing issues of entrepreneurship development in Ukraine. The main purpose of this study is to analyze the impact of current globalization trends on the training of future entrepreneurs in Ukraine. The task is to significantly raise the role and place of entrepreneurship in the economic process of society. Implementation of the model of professional competence of future entrepreneurs in the process of continuous education system, requires scientific management, adaptation to modern conditions of the economic system of democratization and humanization of secondary school. Theoretical and methodological basis of the study is fundamental and modern provisions of economic theory, scientific development of foreign and Ukrainian scientists and specialists in the field of economics. The method of logical generalization is used to substantiate theoretically the importance of the tasks and clarify the key concepts of the study. The training of future professional in entrepreneurship should correspond to the real needs of the dynamic development of the economy and the modern society. In conclusions the author emphasizes the effectiveness of professional training of future entrepreneurs. It improves due to the introduction to the educational process an informative and communicative component to form highly qualified entrepreneurs capable to work in computer networks; those who have business skills; ability to think independently and analyze market situation.